2017
DOI: 10.1016/j.promfg.2017.09.098
|View full text |Cite
|
Sign up to set email alerts
|

Improving mechanical engineering vocabulary through the use of a game

Abstract: In the present paper, we shall firstly show how a learning game to teach basic technical vocabulary can help players to improve their language skills. The benefits this new tool can have on teaching methods and on motivation will then be examined.Postprint (published version

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Cao Chung Weighing an Elephant [123] The Elephant and the Blind Men [123] Simulated real-world 3D-DGBLL [42] Contextual learning RPGs [120] Handheld sensor-based vocabulary games [112] RPG for incidental lexicon acquisition [90] WiCFG [59] Interactive learning environment [100,127] Virtual Knee Surgery by Edheads [126] Scenario-Based Interactive Environment [136] Prêt à négocier [64] The Conference Interpreter [135] Game-Based System for ASL using Kinect [66] Little Ingenius [81] Idiomatico [130] ARCS-based game [70] My Pet Shop [115] ImALeG [94] Kes Sesi [48] Cool Nurse [74] Virtual Reality Assisted Language Learning game [121] Enskill English [124] TALSQ [72] DiMaCA-based application [21] MMORPG-based English Learning Environment (MELE) [84] Spaceteam ESL [71] Competitive Cloze Game [87] Complexity-based competition game [86] SELS [51] Contextual RPG [85] Wordsearch [52] BSL RPG game [105] Table A3.…”
Section: Name Of Game Papersmentioning
confidence: 99%
“…Cao Chung Weighing an Elephant [123] The Elephant and the Blind Men [123] Simulated real-world 3D-DGBLL [42] Contextual learning RPGs [120] Handheld sensor-based vocabulary games [112] RPG for incidental lexicon acquisition [90] WiCFG [59] Interactive learning environment [100,127] Virtual Knee Surgery by Edheads [126] Scenario-Based Interactive Environment [136] Prêt à négocier [64] The Conference Interpreter [135] Game-Based System for ASL using Kinect [66] Little Ingenius [81] Idiomatico [130] ARCS-based game [70] My Pet Shop [115] ImALeG [94] Kes Sesi [48] Cool Nurse [74] Virtual Reality Assisted Language Learning game [121] Enskill English [124] TALSQ [72] DiMaCA-based application [21] MMORPG-based English Learning Environment (MELE) [84] Spaceteam ESL [71] Competitive Cloze Game [87] Complexity-based competition game [86] SELS [51] Contextual RPG [85] Wordsearch [52] BSL RPG game [105] Table A3.…”
Section: Name Of Game Papersmentioning
confidence: 99%
“…Language for Specific Purposes (LSP) Language for Specific Purposes (LSP) involves the use of DGBLL to support technical language learning. While ESP typically provides broad training for teachers, experts in specific fields, such as the Train Your Technical English for Mechanical Engineering http://ijlter.org/index.php/ijlter (TOTEM) project (Lelardeux et al, 2017), develop technical tools to enhance LSP learning. This highlights the role of DGBLL in facilitating targeted language acquisition tailored to specific professional or disciplinary contexts.…”
Section: Cognitive Complexity-based Competition Strategy (Ccbcs)mentioning
confidence: 99%
“…In addition, Polyzi and Moussiades (2023) used the term DGBVL to specifically utilize visual elements and enjoyable experiences and boost self-confidence and curiosity among learners (Rasti, 2021). Addressing the issues of ESP, Lelardeux et al (2017) posited that LSP tailors DGBLL for technical language learning in specific professional contexts. Scholz (2017) noted that SLD shifts emphasis from acquisition to ongoing practical language use, especially in extramural settings.…”
Section: Complex Adaptive System (Cas)mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of mobile learning applications in vocabulary learning has been reported to improve student achievement better than using traditional teaching techniques (Polakova, 2022;Lelardeux, et al, 2017), motivation and engagement of students (Ozan, 2013;Rogers & Price, 2009;Yilmaz & Akpinar, 2011). Moreover, it has been reported that mobile apps are efficient regarding time, place, or circumstances (Xu, Applying MALL to an EFL Listening and Speaking Course: An Action, 2020;Naismith & Corlett, 2006).…”
Section: Introductionmentioning
confidence: 99%